Elucidating the genetic architecture of Adams–Oliver syndrome in a large European cohort. Issue 9 (4th July 2018) - Meester, Josephina A.N.; Sukalo, Maja; Schröder, Kim C.; Schanze, Denny; Baynam, Gareth; Borck, Guntram; Bramswig, Nuria C.; Duman, Duygu; Gilbert‐Dussardier, Brigitte; Holder‐Espinasse, Muriel; Itin, Peter; Johnson, Diana S.; et al.
Abstract: Adams–Oliver syndrome (AOS) is a rare developmental disorder, characterized by scalp aplasia cutis congenita (ACC) and transverse terminal limb defects (TTLD). Autosomal dominant forms of AOS are linked to mutations in ARHGAP31, DLL4, NOTCH1 or RBPJ, while DOCK6 and EOGT underlie autosomal recessive inheritance. Data on the frequency and distribution of mutations in large cohorts are currently limited. The purpose of this study was therefore to comprehensively examine the genetic architecture of AOS in an extensive cohort. Molecular diagnostic screening of 194 AOS/ACC/TTLD probands/families was conducted using next‐generation and/or capillary sequencing analyses. In total, we identified 63 (likely) pathogenic mutations, comprising 56 distinct and 22 novel mutations, providing a molecular diagnosis in 30% of patients. Taken together with previous reports, these findings bring the total number of reported disease variants to 63, with a diagnostic yield of 36% in familial cases. NOTCH1 is the major contributor, underlying 10% of AOS/ACC/TTLD cases, with DLL4 (6%), DOCK6 (6%), ARHGAP31 (3%), EOGT (3%), and RBPJ (2%) representing additional causality in this cohort. We confirm the relevance of genetic screening across the AOS/ACC/TTLD spectrum, highlighting preliminary but important genotype–phenotype correlations. This cohort offers potential for further gene identification to address missing heritability. Abstract : Adams–Oliver syndrome (AOS) is a rare developmental disorder, characterized by scalp aplasia cutis congenita (ACC) and transverse terminal limb defects (TTLD). Molecular diagnostic screening of 194 AOS/ACC/TTLD probands/families was conducted. In total, we identified 63 (likely) pathogenic mutations, providing a molecular diagnosis in 30% of patients. NOTCH1 is the major contributor, underlying 10% of AOS/ACC/TTLD cases, with DLL4 (6%), DOCK6 (6%), ARHGAP31 (3%), EOGT (3%), and RBPJ (2%) representing additional causality in this cohort.